THE INTERNAL FORCES AND STRESSES IN THE BLADE OF A HORIZONTAL BANDSAW AFTER SOLVING THE STATICALLY INDETERMINATE PROBLEM (Innovation in Woodworking Industry and Engineering design, 2026)
The problem of the internal forces and stresses in the blade of a horizontal band-saw isstatically indeterminate in the case of pre-tensioning by a spring. After our solution in a precedingarticle, in this paper the internal forces and stresses in the different parts of the blade areconsidered. Some remarks are addressed to the interpretation of such stresses in the bandsawreferences reviewed. As well, stresses are analyzed relating to bending the blade over the wheelcontours. Additional stresses are also outlined: at the guide rollers, other more bending stresses,as well as stresses due to torsion of the blade, etc.